Study of pulmonary function tests in multitransfused children with beta thalassemia major: an observational study - Shivaswamy, Kavya; Chikkanna, Somashekhar; Singh, Jagdish; Gubbari, Keerthana T. N. (International Journal of Contemporary Pediatrics, 2020)
Background: Thalassemia is a hemoglobinopathy requiring multiple blood transfusions leading to iron deposition in various organs. Abnormalities in pulmonary function in thalassemia major patients have been found in various studies. Our aim was to study pulmonary function tests (PFT) in multitransfused children with beta thalassemia major. Methods: PFT was done in forty beta thalassemia major (TM) patients and forty normal healthy age and sex matched individuals and the results were analyzed. Results: Out of 40 thalassemia major patients, 20 (50%) had normal PFT and the rest 20 (50%) had an abnormal PFT out of which 18 (90%) had restrictive PFT and 2 (10%) had obstructive PFT. Out of 40 controls, all 40 (100%) had normal PFT. Conclusions: Alteration of pulmonary function can be seen even in well-chelated TM patients. The respiratory system should be evaluated annually by PFTs even in asymptomatic patients to prevent pulmonary sequelae.